Loyal wingmen and Artificial Intelligence Development : a state of artDrones are increasingly present in everyday life. Their use has also increased in the fields of security and defense, where they take on the 5D task (Dull, Dirty, Dangerous, Dear and Di - Dugoin-Clément, Christine (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
Drones are increasingly present in everyday life. Their use has also increased in the fields of security and defense, where they take on the 5D task (Dull, Dirty, Dangerous, Dear and Difficult) and help protect men in the performance of risky tasks, as well as enhance the visibility and surveillance of disturbed and/or extended areas. The evolution of drones means the rise of artificial intelligence, especially for the most sophisticated ones, such as Loyal Wingmen. With the Russian invasion of Ukraine, drones are the focus of particular interest, and the US Department of Defense (DoD) place an order for 1,000 collaborative fighter jets by Loyal Wingmen is in the spotlight. In this context, this article will present the main challenges that AI must meet to allow the development of this type of specific drones and will make a state of the art of the development of Loyal Wingmen. Finally, in the light of the issues identified, this paper will propose an industrial development path.